Effects of molecular hydrogen supplementation on fatigue and aerobic capacity in healthy adults: A systematic review and meta-analysis - Zhou, Kaixiang; Liu, Meng; Wang, Yubo; Liu, Haoyang; Manor, Brad; Bao, Dapeng; Zhang, Luyu; Zhou, Junhong (Frontiers in Nutrition, 2023)
Background: Fatigue is oftentimes induced by high-intensity exercise potentially via the exceeded amount of reactive oxygen species, leading to diminished functions (e.g., aerobic capacity) and increased risk of injuries. Studies showed that hydrogen (H2) with antioxidant and anti-inflammatory properties may be a promising strategy to alleviate fatigue and improve aerobic capacity. However, such effects have not been comprehensively characterized. Objective: To systematically assess the effects of intaking H2 on fatigue and aerobic capacity in healthy adults. Methods: The search was conducted in August 2022 in five databases. Studies with randomized controlled or crossover designs that investigated the rating of perceived exertion (RPE), maximal oxygen uptake (V̇O2max), peak oxygen uptake (V̇O2peak), and endurance performance were selected. The data (mean ± standard deviation and sample size) were extracted from the included studies and were converted into the standardized mean difference (SMD). Random-effects meta-analyses were performed. Results: Seventeen publications (19 studies) consisting of 402 participants were included. The pooled effect sizes of H2 on RPE (SMDpooled=-0.38, 95%CI -0.65 to -0.11, p=0.006, I2=33.6.%, p=0.149) and blood lactate (SMDpooled=-0.42, 95% CI -0.72 to -0.12, p=0.006, I2=35.6%, p=0.114) were small and significant with low heterogeneity; but the pooled effect sizes of H2 on V̇O2max and V̇O2peak (SMDpooled=0.09,95% CI -0.10 to 0.29, p=0.333, I2=0%, p=0.998) and endurance performance (SMDpooled=0.01,95% CI -0.23 to 0.25, p=0.946, I2=0%, p>0.999) were not significant and trivial without heterogeneity. Subgroup analysis revealed that the effects of H2 on fatigue were impacted significantly by the training status (i.e., untrained and trained), period of H2 implementation, and exercise types (i.e., continuous and intermittent exercises). Conclusions: This meta-analysis provides moderate evidence that H2 supplementation could alleviate fatigue but not enhance aerobic capacity in healthy adults.